The impac t of a scientific issue aproac h on the scientific and technological literac y of youth and adults - García Ramírez, Natalia Katherine; Martínez Pérez, Leonardo Fabio (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The processes of the scientific and technological literacy (STL) developed with communities of youth and adults do not usually emerge beyond the classroom, these are simply compulsory for obtaining a degree. In such a context, this paper presents the results of a research whose purpose was to analyze the impact of the discussion about controversial aspects of a socioscientific issue (SCI) on the SLT process of a group of youth and adults who studied a secondary school program by cycles in the town of Chia, Cundinamarca (Colombia). Some SCI-based activities related to the pollution caused by the industrial action in the Rio Frio sub-basin river (Cundinamarca, Colombia) were designed and implemented for the analysis. It was found that working with SCI in literacy processes allows the formation of a critical and participatory subject, thus encouraging the learning of science concepts and their relationship with social and technological implications.